Knowledge and Understanding in Forensic Science of the Medical Personnel at Paknamchumphon Hospital and Tungtago Hospital in Chumphon Province - Aranya, Jariya; Seelanan, Parinya (Suan Dusit Graduate School Academic Journal, 2022)
The study aimed to compare the knowledge and understanding in forensic science of the medical personnel at Paknamchumphon hospital and Tungtago hospital in Chumphon province. The quantitative research was performed by using the questionnaire reviewed under the index of item objective congruence (IOC). The sample included 68 medical personnel selected by purposive sampling and the statistical analysis and hypotheses testing were conducted with t-test. The results showed that knowledge and understanding in forensic science of the medical personnel of these two hospitals were found at the good level. The knowledge and understanding in the autopsy were found at the highest level while the knowledge and understanding in identity identification were found at the lowest level. Based on the comparison study between medical doctors and nurses in the hospitals, it was found that (1) Different working status affected knowledge and understanding in wound documentation. The medical doctors were more knowledgeable in wound documentation than nurses and nurses were more knowledgeable in victim identification than the medical doctors. (2) Different working experiences revealed different personnel's knowledge and understanding of 4 areas, except the identity identification. (3) Different training courses for the personnel clearly demonstrated the difference in knowledge and understanding for the areas of wound documentation and identity identification. (4) The medical personnel working in different hospitals had different knowledge and understanding. The medical personnel working at Paknamchumphon Hospital had more knowledge and understanding than the medical personnel working at Thungtako Hospital in terms of identity identification at the statistical significance level of 0.05. In conclusion, overall knowledge and understanding in forensic science of the hospital personnel were equivalent. The identity identification should be enhanced as it affected the knowledge and understanding in forensic science of the medical personnel.